2017
DOI: 10.1016/j.phytochem.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative cyclodepsipeptides from the marine actinomycete Streptomyces sp. P11-23B downregulating the tumor metabolic enzymes of glycolysis, glutaminolysis, and lipogenesis

Abstract: Two cyclodepsipeptides and a known cyclodepsipeptide valinomycin were isolated from a culture of the marine actinomycete Streptomyces sp. P11-23B. Their structures were established based on NMR, HRESIMS, and MS-MS spectroscopic interpretation as well as by chemical degradation. Both streptodepsipeptides P11A and P11B inhibited proliferation of different glioma cell lines, with IC values ranging from 0.1 μM to 1.4 μM. Streptodepsipeptide P11A was found to block the cell cycle at the G/G phase and induce apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 33 publications
2
80
0
Order By: Relevance
“…tumour metabolic enzymes, HK2, PFKFB3, PKM2, LLS and FASN were downregulated by 14. 23 A bioassay-guided investigation of a fermentation culture of Pseudonocardia carboxydivorans M-227, which was collected from water at a depth of 3000 m in the Aviles Canyon (Cantabrian Sea, Biscay Bay), yielded two antibiotics, branimycins B 16 and C 17 (ref. 24) that displayed moderate to signicant antibacterial activities against 28 strains (18 Gram-positive; 10 Gram-negative) with MICs ranging from 1 to >160 mg mL À1 .…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
“…tumour metabolic enzymes, HK2, PFKFB3, PKM2, LLS and FASN were downregulated by 14. 23 A bioassay-guided investigation of a fermentation culture of Pseudonocardia carboxydivorans M-227, which was collected from water at a depth of 3000 m in the Aviles Canyon (Cantabrian Sea, Biscay Bay), yielded two antibiotics, branimycins B 16 and C 17 (ref. 24) that displayed moderate to signicant antibacterial activities against 28 strains (18 Gram-positive; 10 Gram-negative) with MICs ranging from 1 to >160 mg mL À1 .…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
“…Therefore, the effect of TLA on the expression levels of glioma metabolic enzymes, including HK2, PFKFB3, PKM2, and LDH5 in the glycolysis, GLS in the glutaminolysis, and FASN in the lipogenesis, was further investigated. A previous study demonstrated that these metabolic regulators were highly expressed in U87MG and U251 cells [34]. Therefore, the effect of TLA on the expression of these regulators in U87MG and U251 cells was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Both P11A and P11B can inhibit the proliferation of several glioma cell lines, with the IC 50 values of 0.1 to 1.4 μM [53]. Streptodepsipeptide P11A induced apoptosis and inhibited the cell cycle at the G0/G1 phase in glioma cells [53]. Further study showed that streptodepsipeptide P11A downregulated the expressions of important tumor metabolic enzymes such as HK2, GLS, PKM2, PFKFB3, and FASN [53].…”
Section: Anticancer Peptides Induce Apoptosis With Unknown Mechanismmentioning
confidence: 99%
“…P11-23B (CN106167517) [9]. Both P11A and P11B can inhibit the proliferation of several glioma cell lines, with the IC 50 values of 0.1 to 1.4 μM [53]. Streptodepsipeptide P11A induced apoptosis and inhibited the cell cycle at the G0/G1 phase in glioma cells [53].…”
Section: Anticancer Peptides Induce Apoptosis With Unknown Mechanismmentioning
confidence: 99%
See 1 more Smart Citation